A (re)produção da segregação socioespacial na região metropolitana de Aracaju(SE) : interfaces da ação do estado e do capital - Santos, Mário Jorge Silva (2018)
Socio-spatial segregation can be discussed under various aspects. The socio-spatial differentiations in the cities are becoming increasingly stressed, observing the constitution of segregative processes which shred and constitute spaces of wealth and poverty. The capacity of appropriation of space by social groups produces a peculiar spatial organization, and it is possible to identify the very dynamics of spatially printed social relations. It is important to understand that capitalist reproduction finds in the State the vehicle of domination of the working class, being a facilitator of enrichment for the benefit of the ruling class. It is the essential institutional apparatus of class strategies which make cities suitable for capitalist accumulation in all aspects. This process is strengthened by decisions, actions and practices of a part of society which struggles for maintaining the separation of social classes. For Carlos (2013), socio-spatial segregation is a contradictory result of the social production of the city and its private appropriation. The existence of private property of wealth supported by a class society and the constitution of space as a trade value generate the struggle for the "right to the city." On these theoretical assumptions, the present thesis aims to analyze the (re) production of socio-spatial segregation in the RMA, linking this production to the action of the State and capital that, over time (1968-2014) built housing development in the region through housing policies, resulting in the division of space by social classes and the transformation of housing into a commodity, which serves the logic of reproduction of real estate finance capital. The metropolitan region of Aracaju (RMA), located in the State of Sergipe, northeast of Brazil, is a regional urban agglomerate legally established and constituted by the municipalities of Aracaju, Barra do Coqueiros, Nossa Senhora do Socorro and São Cristóvão. The dimension and urban growth of Aracaju, the main city of the metropolitan region, advanced in its spatial expression towards the neighboring municipalities, forming a single urban spot, a production marked by a process of fragmentation, hierarchization and socio-spatial segregation. The housing policies of COHAB / SE, INOCOOP / BASE, PAR and the PMCMV are taken to explain this process of production of the segregated regional urban space, subordinating its production to the logic of the capitalist system that, in interface with the State, promote inequalities in conditions housing and socioeconomic conditions among the municipalities that form the region, delimiting real territories of socio-spatial segregation in the RMA. Nowadays, the PMCMV is an instrument of capital for the continuity of this process, its contradictions as a housing policy are expressed since its housing developments (2009-2014) fractionalize space, elitize areas, promote population peripherization and (re) produce socio-spatial segregation in historically segregated territories. The action of the State and capital in the construction of these housing developments, therefore, produces a metropolitan region segregated with determinations imposed on a separation in the living conditions of the populations living in these territories, separating people by their class condition and structuring, via State, the necessary conditions for the commodification of space in the metropolitan region, (re) producing even more socio-spatial segregation.